Green Logistic and Sustainable Electronic Products Packaging; Consumers Perspective - Dilip Bhujbal , Digvijay; Shafighi, Najla (International Journal of Business and Social Science Research, 2022)
The purpose of this study is to examine the customer perception and the impact of several on green logistics. More specifically, we looked at how customers' perceptions of green packaging, government assistance for recycling materials and trash management, eco-products, education on waste recycling, and waste management awareness affect green logistics. A quantitative approach using a questionnaire is employed. A total of 124 usable surveys is collected. Using the regression analysis, the findings reveal that green packaging, Eco-products & education are strongly and positively influenced by green logistics. However, Government support moderately and positively influences green logistics.